TINJAUAN EKOLOGIS TERHADAP SEBARAN KERUANGAN KUALITAS AIR TANAH BEBAS DI KOTA PURWOKERTO JAWA TENGAH - Susatyo Adhi Pramono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2006)
AbstractThis research was conducted in Purwokerto and its environs. It aims to find out the impact of differences in environmental conditions resulting from physical urban development on the distribution in quality of groundwater in Purwokerto. This research adopted a combination of two kinds of research, namely a survey and descriptive, comparative research with observation in the field. The survey was used to measure the required physical data. The descriptive, comparative research was used to find out the effects of environmental factors on the quality of groundwater.The data were analyzed using 4 methods of analysis, namely temporal analysis, spatial analysis, ecological analysis, and statistical analysis in order to find out the effects of environmental factors on the distribution in quality of ground water in Purwokerto.Results of the research indicate a progressive deterioration in quality of the groundwater in the research site. The temporal analysis proves that the deterioration in quality happens concurrently with the increase of urban development. From 10 elements of water quality under examination, there are 4 elements that have exceeded the standard water quality of grade B. The spatial analysis proves that the quality of water in the northern part of the town is better than that in the centre and the southern part. This means that the environmental conditions of the urban area contribute to the deterioration in quality of groundwater in Purwokerto.From the statistical analysis it is found that the density of building and population as well as the depth of groundwater contribute to the derioration in water quality. In addition to these 3 variables, other variables that affect water quality are sanitary facilities, environmental conditions and land use.Â Keywords: Density of residential areas, land use. quality of groundwater